2022
DOI: 10.1111/jace.18542
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal grain growth in DC flash sintered 3‐mol% yttria‐stabilized zirconia ceramics

Abstract: The origin of nonuniform microstructure and abnormal grain growth (AGG) was investigated in flash sintered 3 mol% yttria‐stabilized zirconia (3YSZ) ceramics. The microstructural homogeneity decreased with increasing direct current (DC) density and with dwell time in a flash state, eventually resulting in AGG in the specimen core, the first observation of AGG in 3YSZ. Abnormal grains up to 100 μm in size emerged when the DC density was ≥160 mA/mm2, and the specimen's density exceeded 99% of theoretical, startin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The acceleration of the grain growth under an electric field was explained in terms of the segregation of YZr$Y_{Zr}^\prime $ along the grain boundaries and the generation of space‐charge layers due to oxygen vacancies. Other studies have indicated that the grain growth is enhanced during the flash event as a result of the generation of defects such as oxygen vacancies 28–31,34,36,38,39,45 . In contrast, opposite results stating that the electric field and current suppress the grain growth have also been reported 33,35,40,43,44 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The acceleration of the grain growth under an electric field was explained in terms of the segregation of YZr$Y_{Zr}^\prime $ along the grain boundaries and the generation of space‐charge layers due to oxygen vacancies. Other studies have indicated that the grain growth is enhanced during the flash event as a result of the generation of defects such as oxygen vacancies 28–31,34,36,38,39,45 . In contrast, opposite results stating that the electric field and current suppress the grain growth have also been reported 33,35,40,43,44 .…”
Section: Introductionmentioning
confidence: 99%
“…To clarify the athermal effects on the diffusion phenomena during a flash event, the effects of the electric field and current on the microstructures have been investigated in the flash sintering of zirconia systems 27,29–31,33–45 . However, conflicting results have been described even for the same zirconia system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the field-assisted sintering and annealing of ceramics had demonstrated that an electric field can promote neck formation and refine grains. [8][9][10] Noticeably, it was directly observed that the electric field can drive directional movement of GBs in ceramics, such as alumina (Al 2 O 3 ) 11 and strontium titanate. 12 In addition, ceramics can be used to make key components in microelectronic packages and integrated circuits 13 ; recently, there has been extensive attention to the material reliability of ceramics, including grain morphology and distribution characteristics, especially the anisotropic properties of ceramics are in dependence on orientation and grain size.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, stress 6 and thermal gradient 7 can be the driving force for GB migration and grain evolution, accompanied by the capillary driving force influence. Moreover, the field‐assisted sintering and annealing of ceramics had demonstrated that an electric field can promote neck formation and refine grains 8–10 . Noticeably, it was directly observed that the electric field can drive directional movement of GBs in ceramics, such as alumina (Al 2 O 3 ) 11 and strontium titanate 12 .…”
Section: Introductionmentioning
confidence: 99%